Forgotten exogenous corticosteroid as a cause of central serous chorioretinopathy - Paul W Hardwig (Dove Medical Press, 2008)
Paul W Hardwig1, Amila O Silva2, Jose S Pulido11Department of Ophthalmology, Mayo Clinic, Rochester, MN, USA; 2Kaiser Permanente Fontana Medical Center, Fontana, CA, USAAbstract: Central serous chorioretinopathy (CSCR) is an idiopathic ocular condition – first described in 1866 – that is well known to ophthalmologists. It is less well known to other practitioners. Glucocorticoids have been strongly implicated as a pathogenic factor. We report three patients who developed CSCR following exogenous administration of corticosteroid. Because our patients did not suspect the use of corticosteroid to be important or causative, they did not volunteer the historical detail, and admitted to exogenous corticosteroid injection only with intensive questioning. For their part, physicians should be cognizant of the risk of corticosteroid-induced CSCR, particularly in patients with a prior history of the potentially sight-threatening disease. The development of CSCR is an important iatrogenic and often unrecognized side effect of exogenously administered corticosteroid.Keywords: exogenous corticosteroid, ocular complication, central serous chorioretinopathy